KRITIK SOSIAL DAN NILAI PENDIDIKAN KARAKTER DALAM NASKAH DRAMA THE DUKUN DAN RELEVANSINYA DENGAN PEMBELAJARAN SASTRA DI SEKOLAH MENENGAH ATAS - Wahid Ibnu Nugroho; Sarwiji Suwandi; Sri Hastuti (Universitas Sebelas Maret, 2020)
This research aims to describe social criticism; the value of character building in drama script “the dukun” by Dukut Wahyu Nugroho, and the relevance of drama script “the dukun” by Dukut Wahyu Nugroho as literary teaching material in the senior high school. The sampling technique used is purposive for the sample is chosen based on certain purpose in order to reach the objective of this research. The source of data is drama script “the dukun” by dukut wahyu nugroho and informant, therefore the data are collected by document review and interview. The test validity of the research data used triangulation of theory and triangulation of source. The analysis of data was done by interactive analysis which is consisting of data collection, data reduction, data presentation, and conclusion. The result of this research describes that the drama script “the dukun” besides has a simple plot and can be shown in senior high school learning, also gives a deep moral message to the reader. Story plotting that coherent can be used as a research object to add insight of the literature sociology, so can be implemented in learning Bahasa Indonesia in senior high school and keep mind to the SK/KD which is used.